Buruli ulcer in southern Côte D’ivoire: dynamic schemes of perception and interpretation of modes of transmission - Mosi, L.; Konan, D.O.; Fokou, G.; Dassi, C.; Narh, C.A.; Quaye, C.; Saric, j; Abe, N.N.; Bonfoh, B. (Journal of Biosocial Science, 2018)
Buruli ulcer (BU) belongs to the group of neglected tropical diseases and constitutes a public health problem in many rural communities in Côte d’Ivoire. The transmission patterns of this skin infection are poorly defined, hence the current study aimed to contribute to the understanding, perceptions and interpretations of its mode of transmission using a socio-environmental approach. Social and environmental risk factors that may expose people to infection, and the dynamics of local transfer of knowledge and practices related to BU, were assessed in two endemic locations in southern Côte d’Ivoire, i.e. Taabo and Daloa. Data were generated by the administration of a household questionnaire (N= 500) between February and June 2012 to assess how the population perceived transmission of BU, focus group discussions with local communities (N= 8) to analyse ideologies regarding transmission patterns and semi-structured interviews with patients or their parents, former BU patients and traditional healers (N= 30). The interviewees’ empirical knowledge of the disease was found to be close to its biomedical description. Their aetiological perception of the disease was linked to natural (e.g. dirty water, insects) and supernatural (e.g. witchcraft, fate) causes. Some informants attributed the spread of the disease to recently immigrated neighbouring communities whose arrival coincided with an increase in reported BU cases. However, the general consensus seemed to be that the main mode of transmission was contact with infested soil or ulcerated wounds. The participants were aware that BU was a socio-environmental problem in these endemic areas, offering a good starting point for educational campaigns for at-risk communities. Buruli ulcer control programmes should therefore include educational campaigns and Water, Sanitation and Hygiene (WASH) interventions for those at risk in affected communities.
Research Article
Keywords: Buruli ulcer; Perception; Côte d’Ivoire